2018
DOI: 10.1302/0301-620x.100b6.bjj-2017-0736.r3
|View full text |Cite
|
Sign up to set email alerts
|

Continual near-infrared spectroscopy monitoring in the injured lower limb and acute compartment syndrome

Abstract: NIRS oximetry might be used to aid the assessment and management of patients with ACS. Sustained hyperaemia is consistent with the absence of ACS in injured legs. Loss of the hyperaemic differential warrants heightened surveillance. NIRS values in at least one injured compartment(s) were > 3% below the uninjured contralateral compartment(s) in all seven patients with ACS. Additional interventional studies are required to validate the use of NIRS for ACS monitoring. Cite this article: Bone Joint J 2018;100-B:78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…NIRS values were typically >3% higher in injured limbs without ACS than in uninjured compartments. In contrast, all seven limbs with clinically diagnosed ACS had at least one compartment where NIRS values were 3% or more below an uninjured control compartment [15].…”
Section: Nirsmentioning
confidence: 84%
See 2 more Smart Citations
“…NIRS values were typically >3% higher in injured limbs without ACS than in uninjured compartments. In contrast, all seven limbs with clinically diagnosed ACS had at least one compartment where NIRS values were 3% or more below an uninjured control compartment [15].…”
Section: Nirsmentioning
confidence: 84%
“…Two recent papers have reported on continuous NIRS in a clinical setting. Shuler et al [15] reported on 109 patients who had NIRS recording of the tissue perfusion in all four leg compartments of both legs (anterior, lateral, superficial posterior, and deep posterior): 86 had unilateral leg injuries while 23 did not. Mean NIRS values were between 72% and 78% in injured legs, between 69% and 72% in uninjured legs, and between 71% and 73% in bilaterally uninjured legs.…”
Section: Nirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential advantages are without question, but the utilisation of these techniques is thus far not been sufficiently validated in the literature. Near-infrared spectroscopy utilises a probe placed on the skin to determine the degree of oxygenated haemoglobin in the muscle tissues [97][98][99][100]. It has been shown to correlate well with tissue pressures from experimental data [97], as well as in healthy human volunteers [98].…”
Section: Future Directionsmentioning
confidence: 99%
“…In 2007, a paediatric case report utilised NIRS in the diagnosis of ACS in a one month old infant, with a NIRS value of 15% in the involved limb versus 40–50% in the uninvolved limb [52]. In patients with ACS, Shuler et al found NIRS values from at least one compartment to be more than 3% below an uninjured control compartment [53]. They advocated simultaneous monitoring of the same compartment on the contralateral limb in order to provide a control.…”
Section: Introductionmentioning
confidence: 99%